Subacute sclerosing panencephalitis with an atypical presentation: A case report - Teber, Serap; Sezer, Taner; Kafalı, Mehpare; Deda, Gülhis (Journal of Pediatric Neurology, 2011)
Subacute sclerosing panencephalitis is almost always fatal with a varying clinical course of illness. It is characterized by slow progression and rarely manifests with a fulminant and rapid course. Atypical presentations such as generalized seizures, visual loss, hemiparesis, non-convulsive status epilepticus and isolated extrapyramidal symptoms can be observed rarely. We report an 11-year-old boy presenting with atypical symptoms initially such as complex partial seizures, chorea and electrographic status epilepticus. The patient was lost within 5 months, which is suitable for a fulminant course. Children presenting with atypical acute or subacute neurologic symptoms should be examined for subacute sclerosing panencephalitis, especially if they have no risk factors for hereditary neurodegenerative and/or neurometabolic diseases.
Keywords: SSPE; atypical presentation; chorea; non-convulsive status epilepticus